THE NEGLECTED EDUCATION CONTRIBUTION OF THE ISLAMIC BOARDING SCHOOL (A CASE STUDY OF KABUPATEN HULU SUNGAI SELATAN, SOUTH KALIMANTAN, INDONESIA) - Ambar Teguh Sulistiyani; Samodra Wibawa; I Made Krisnajaya; Kristi Yuliani (Islam Futura, 2019)
This article would like to discuss the neglected role of Islamic Boarding School (IBS) in one of the biggest Muslim country in the world.  As a case study of Kabupaten Hulu Sungai Selatan (HSS), South Kalimantan - Indonesia, both of primary and secondary data were obtained from the local HSS government, IBS stakeholders and the HSS’s community. This study used Focus Group Discussion, in depth interview, and collect secondary data. Using the descriptive qualitative approach, this study is attempted to examine the role of IBS in national education system. This study tries to answer some question e.g. why the education index has been stagnant around 6 years, what are the differences between two types of IBS, how the Policy Affirmation of IBS graduate can improve the system, and what is the implication of the school formalization. Hence, as the research result, this paper proposes the Flowchart Design of IBS Education.